Review: Flavonoids, their types, chemistry and therapeutic efficacy - Fatima Saiwan Sabah ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
In recent years, interest in plants and their contents of various compounds has increased, which are secondary metabolites of plants, and among these compounds are flavonoids. Flavonoids are known to contain aromatic rings that carry a number of hydroxyl groups and are found in all parts of plants such as leaves, fruits and roots. They appear in the form of aglycones, glycosides and methylated derivatives. They are used as antioxidants, anticancers, antibacterials, heart protective factors, anti-inflammatories, and the immune system Strengthening and protecting the skin from UV rays and an interesting candidate for pharmaceutical and medical application. A few decades ago, research studies focused on flavonoids of medicinal plant species have increased significantly due to Its various benefits for human health.